Change in Physical Activity During the Coronavirus Disease 2019 Lockdown in Norway: The Buffering Effect of Resilience on Mental Health - Anyan, Frederick; Hjemdal, Odin; Ernstsen, Linda; Havnen, Audun (Frontiers in Psychology, 2020)
Imposition of lockdown restrictions during COVID-19 pandemic were sudden, unprecedented and dramatically changed the life of many people who were confined to their homes with reduced movement and access to fitness training facilities. Studies have reported significant associations between physical inactivity, sedentary behavior and common mental health problems. The present study analyzed the relation between participants’ reports of change in physical activity (reduced, unchanged or increased) and symptoms of anxiety and depression during the COVID-19 pandemic lockdown in Norway in the time period March 12th, 2020 to June 15th, 2020. It also investigated how different levels of resilience influenced the relation between change in physical activity level and symptoms of anxiety and depression. A cross-sectional survey design was used. Participants (N = 1 314; Females = 31%) were members of an endurance sports organization aged between 18 and 81 years old (M = 49 years; SD = 11.50 years). Participants completed the Resilience Scale for Adults, the Hospital, Anxiety and Depression Scale, and reported their changes in physical activity after lockdown restrictions were implemented on March 12th, 2020. Analysis of variance investigated mean differences between participants and whether different levels of resilience influenced self-reported change in physical activity level, symptoms of anxiety and depression. The main and interaction effects of change in physical activity and resilience were significantly associated with symptoms of depression. For symptoms of anxiety, only the main effect of resilience and the interaction effect were significant. Results further showed that, resilience was an important factor that influenced the levels of change in physical activity. High levels of resilience were associated with lower symptoms of anxiety and depression in reduced, unchanged and increased physical activity subgroups during the COVID-19 lockdown. Promoting physical activity while boosting resilience factors such as confidence in own ability and drawing on the social support of even the reduced social networks or connections while under lockdown, can protect against common mental health problems.